Stress tests and the countercyclical capital buffer: The UK experience. (23rd September 2020) - Kohn, Donald
Abstract: The stress tests were a major innovation growing out of the Global Financial Crisis (GFC). Their objective is to assure that banks have enough capital to allow them to continue to support the economy by making loans to households and businesses even after a severe adverse shock has hit the economy—in marked contrast to the experience of the GFC when sharp restrictions on credit availability through banks and markets made a bad economic situation much worse. In my talk, I will (a) take a deeper dive into the causes and consequences of procyclical risk‐based bank capital and the role the Financial Policy Committee at the Bank of England (FPC) envisions for the countercyclical capital buffer rate (CCyB), informed by stress tests, in countering this tendency, (b) discuss how the FPC has used the CCyB and stress tests in practice, and (c) end with some challenges for the research agenda that would help the FPC be even more efficient and effective.